Shock-Induced Mesoparticles and Turbulence Occurrence - Tatiana A. Khantuleva; Yurii I. Meshcheryakov (Particles, 2022)
The development of a new approach to describe turbulent motions in condensed matter on the basis of nonlocal modeling of highly non-equilibrium processes in open systems is performed in parallel with an experiment studying the mesostructure of dynamically deformed solids. The shock-induced mesostructure formation inside the propagating waveform registered in real time allows the transient stages of non-equilibrium processes to be qualitatively and quantitatively revealed. A new nonlocal approach, developed on the basis of the nonlocal and retarded transport equations obtained within the non-equilibrium statistical physics, is used to describe the occurrence of turbulence. Within the approach, the reason for the transition to turbulence is that the non-equilibrium spatiotemporal correlation function generates the dynamic structures in the form of finite-size clusters on the mesoscale, with almost identical values of macroscopic densities moving as almost solid particles that can interact and rotate. The fragmentation of spatiotemporal correlations upon impact forms the mesoparticles that move at different speeds and transfer mass, momentum and energy-like wave packets. The movements recorded simultaneously at two scale levels indicate the energy exchange between them. Its description required a redefinition of the concept of energy far from local thermodynamic equilibrium. The experimental results show that the irreversible part of the dynamic mesostructure remains frozen into material as a new defect.